Remotely Delivered Monitoring and Management of Diabetes-Related Foot Disease: An Overview of Systematic Reviews. (January 2023) - Drovandi, Aaron; Wong, Shannon; Seng, Leonard; Crowley, Benjamin; Alahakoon, Chanika; Banwait, Jasmin; Fernando, Malindu E.; Golledge, Jonathan
Background: Diabetes-related foot disease (DFD) management requires input from multiple healthcare professionals, and has worse outcomes for people living in remote localities by comparison to urban areas. Remotely delivered healthcare may reduce this disparity. This overview summarizes current evidence on the effectiveness, stakeholder perceptions, and cost-effectiveness of remotely delivered healthcare for DFD. Methods: A search of 5 databases was conducted to identify systematic reviews published between January 2000 and June 2020. Eligible reviews were those evaluating remotely delivered monitoring or management of patients at risk of or with active DFD, or clinicians managing these patients. Risk of bias was assessed using the AMSTAR-2 tool. Results: Eight reviews were eligible for inclusion, including 88 primary studies and 8509 participants, of which 36 studies involving 4357 participants evaluated remotely delivered monitoring or management of DFD. Only one review had a low risk of bias, with most reviews demonstrating limited search strategies and poor reporting of participants. Evidence on effectiveness was mixed, with meta-analyses demonstrating long-term ulcer healing and mortality were not significantly different between telehealth and standard care groups, although the lower-limb amputation rate was significantly decreased in one meta-analysis. Perceptions of telehealth by patients and clinicians were generally positive, whilst acknowledging limitations relating to access and use. Cost-effectiveness data were limited, with poor reporting preventing clear conclusions. Conclusions: Remotely delivered healthcare of DFD is well received by patients and clinicians, but its effectiveness is unclear. High quality trials are needed to evaluate the risks and benefits of remotely delivered DFD management.